IMPLEMENTASI DESAIN JARINGAN HOTSPOT BERBASIS MIKROTIK DENGAN METODE NDLC (NETWORK DEVELOPMENT LIFE CYCLE) PADA PT KIRANA PERMATA - Tamsir Ariyadi; Timur Dali Purwanto; Muhamad Malik Fajar (LPPM Universitas Putera Batam, 2023)
In this technological development the need for the internet is no longer a foreign thing for the community. With the internet that can connect to each other between one network to a number of networks in the world. Internet use cannot be separated from the existence of the internet service provider itself. To be able to connect to the internet network, a Hotspot facility is needed as a connectivity connecting access to the internet network. The purpose of this study is to design a Hotspot network to increase the efficiency of using computer networks at PT Kirana Permata. In designing this network design using the NDLC method which can be used as a development of network infrastructure to be more optimal. So that the system can run optimally, settings are made on the routerboard which is used as an internet connection from the ISP to the internet user network. For this reason, a network topology that has been designed to be implemented on PT Kirana Permata's computer network is used. So it is hoped that the network topology design can make computer networks more structured. Even so, monitoring still needs to be done to observe data traffic as a network monitor so that it can run as smoothly as expected. This network design plan produces a new network topology that is more efficient and flexible. With the Hotspot network at PT Kirana Permata, the use of the internet network is more accessible for guests and employes.